Espaço e identidade em crônicas de Alexandra Lucas Coelho - Ribeiro, Mariana Letícia (Universidade Federal de São Carlos, 2018)
The purpose of this study is to observe, analyze and understand, through the chronicle and travel literature structures, as well as textual strategies concerning the narrator’s perspective, and, more specifically, intertextuality and polyphony, if and how Alexandra Lucas Coelho deals, in Vai, Brasil (2015) with the concept of collective and individual identity related to space. That way, this work takes into consideration not only theories and studies about intertextuality, travel literature and the chronicle, but also about the representation of space in literature and the geographical concept of space, which involves the relation between itself and man, and also the notions of movement/travel, territory, distance, frontiers, and globalization. Some of these theories and studies are borrowed from Genette (19--), Antonio Candido (1992), Jorge de Sá (1985), Compagnon (1996), Jenny (1979), Bakhtin (2013), Fernando Cristóvão (2002, 2010), John Urry (2001), e Annabela Rita (2007), Doreen Massey (2009), Milton Santos (2000, 2006), Michel De Certeau (1994), Yi-Fu Tuan (1983) e Ozíris Borges Filho (2007). That said, it is possible to divide the chronicles from Vai, Brasil in three big parts that consist in three different moments of the author’s view about the space observed: the ones in which there is a first distance between the author and the space, the ones that show a moment of identifying and taking distance in a critical way, and, at last, the chronicles referring to recognizing the other. This division makes it possible to understand the way in which Coelho’s point of view is divided between a tourist one, that chooses what or who to identify with, and an anthropologist one, since she permits herself take a step back from her conceptions about the country observed and also open a place to the local people’s voices. Moreover, the Portuguese writer presents her own definition of identity, which depends on History and on what the globalized world can offer – or, sometimes, impose on space and its individuals –, but it also depends on the fact that space is always in movement, natural or promoted by men, who gives it value and meaning, and, for that reason, are the main element of space composition, and, consequently, conscientiously or not, of their own identity.
Space and identity in Alexandra Lucas Coelho's chronicles
Keywords: Literatura de viagens; Espaço; Identidade; Crônica; Globalização; Vozes; Travel Literature; Space; Identity; Chronicle; Globalization; Voices; LINGUISTICA, LETRAS E ARTES::LETRAS::LITERATURA COMPARADA; LINGUISTICA, LETRAS E ARTES::LETRAS